Sucrose transporter plays a role in phloem loading in CMV-infected melon plants that are defined as symplastic loaders - Gil, Lidor; Yaron, Imry; Shalitin, Dror; Sauer, Norbert; Turgeon, Robert; Wolf, Shmuel (Plant Journal, 2011)
Based on the high density of plasmodesmata interconnecting the intermediary cells and their neighboring phloem parenchyma or bundle-sheath cells, and based on the insensitivity to the sucrose transport inhibitor p- chloromercuribenzenesulfonic acid (PCMBS), cucurbits have been concluded to be symplastic loaders. In the present study, we identified and characterized the full-length sequence of sucrose transporter gene (CmSUT1) from melon (Cucumis melo L. cv. Hale's best jumbo). In vitro experiments confirmed that the identified gene product has sucrose transporter activity in baker's yeast. Healthy and cucumber mosaic virus (CMV)-infected melon plants were employed to examine sucrose transporter activity in planta. Pretreatment with PCMBS inhibited loading of newly fixed CO into minor veins of CMV-infected plants. Moreover, CMV infection caused significant increase in CmSUT1 transcripts expression, mainly in vascular bundles of minor veins, which was associated with elevated sucrose content in phloem sap collected from source-leaf petioles. We propose that cucurbit plants contain the machinery for apoplastic phloem loading and that CMV infection causes a quantitative shift in the mode by which photoassimilates are loaded into the sieve tube. © 2011 Blackwell Publishing Ltd.
Keywords: cucumber mosaic virus; Cucumis melo; cucurbit; phloem loading; sucrose transporter